Riociguat, a soluble guanylate cyclase stimulator, ameliorates right ventricular contraction in pulmonary arterial hypertension - Mitsushige Murata; Takashi Kawakami; Masaharu Kataoka; Takashi Kohno; Yuji Itabashi; Keiichi Fukuda (Pulmonary Circulation, 2017)
Riociguat is a soluble guanylate cyclase stimulator used for pulmonary hypertension (PH) treatment. We evaluated right ventricular (RV) contractile function in 27 PH patients receiving riociguat. A comparison of pre- and post-administration echocardiographic studies demonstrated significantly improved RV strain after riociguat treatment, even after adjusting for RV afterload.